Pengaruh Kualitas Produk, Kualitas Pelayanan, dan Harga Terhadap Kepuasan Konsumen pada Restoran Pizza Hut Mall Mega Bekasi - Randy Reliantama Tanamas; Suwardi Suwardi (Universitas 45 Surabaya, 2024)
The fastfood business is one of the most competitive and rapidly growing businesses in Indonesia. people in urban areas, namely the tendency to get something instantly, one of which is fast food. This study aims to determine the effect of the variables Product Quality, Service Quality, and Price on Consumer Satisfaction at Pizza Hut restaurants. The sample was chosen by consumers who have purchased and eaten Pizza Hut at Mall Mega Bekasi. The data used is primary data, data collection is done by distributing questionnaires to 100 respondents. The test tools used are validity test, reliability test, classic assumption test, multiple linear regression analysis, t test, f test, and the coefficient of determination and the data is processed using SPSS v25 software. The results of this study indicate that the product quality variable partially has no significant effect on customer satisfaction, the service quality variable partially has a significant effect on customer satisfaction, the price variable partially has a significant effect on customer satisfaction while product quality, service quality and price simultaneously have an effect on satisfaction Pizza Hut Mall Mega Bekasi restaurant customers.